Mineralization and Fixed Stable Carbon Isotopic Characteristics of Organic Carbon in Cotton Fields with Different Continuous Cropping Years - Xinyu Ma; Lu Gong; Yuxin Yang; Zhaolong Ding; Xinzhu Li (Agronomy, 2023)
The oasis carbon pool in arid zones is an important part of the global carbon pool. There is a soil organic carbon (SOC)–soil–CO2–soil inorganic carbon (SIC) balanced system in the soil, which facilitates the change from soil organic carbon to soil inorganic carbon. A small change in the soil carbon pool can affect the overall global carbon balance, thus affecting the conversion of soil carbon in terrestrial ecosystems. In this study, the change from soil organic carbon to soil inorganic carbon (SIC) was obtained by measuring the δ13C values of SIC and CO2 in combination with stable carbon isotope techniques in cotton fields with different continuous cropping years, in the Alar Reclamation Area. Additionally, this was combined with redundancy analysis to reveal the effects of different physicochemical factors on the change amount. The results showed that the soil inorganic carbon content along the soil profile showed an increasing trend, while the soil organic carbon content was the opposite; the δ13C of SIC in the 0–20 and 60–80 cm soil layers were the highest in the 10a continuous cotton field soil, which were −22.24 and −21.86‰, respectively, and significantly different to other types (p < 0.05). The fixed carbon values in the barren, 5a, 10a, 20a, and 30a continuous cotton fields were 0.53, 0.17, 0.11, 0.13 and 0.33 g·kg−1, respectively; the corresponding amounts of CO2 fixed from soil respiration were 0.33, 0.11, 0.08, 0.05, and 0.25 g·kg−1; the amounts of CO2 from the atmosphere were 0.20, 0.06, 0.03, 0.02, and 0.09 g·kg−1; and the oxidative decomposition of CO2 by SOC were 0.17, 0.06, 0.04, 0.26, and 0.12 g·kg−1, respectively, indicating that the contribution of SOC was more in the barren field and 30a cotton field. Comparing the sources of fixed CO2, we found that the amount of fixed soil from barren fields and 30a was high from atmospheric CO2, while the contribution of SOC was low. Furthermore, the amount of fixed CO2 of 20a from SOC was high, and the atmospheric contribution was low. The main physicochemical factors that affecting the amount of soil SOC changed to SIC were soil water content, readily available carbon dioxide, and microbial biomass carbon.